1999
DOI: 10.1108/00242539910299005
|View full text |Cite
|
Sign up to set email alerts
|

Resource sharing among agricultural libraries in Malaysia

Abstract: Investigates resource sharing activities undertaken by agricultural libraries in Malaysia. It was found that resource sharing was basically limited to interlibrary lending and document delivery activities. On the average, each scientist from the participating research institutions made 1.25 document delivery and interlibrary loan requests per annum. Nearly 74 percent of these requests were met from local libraries. The participating libraries preferred to make their overseas document delivery requests to the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…It is interesting to note that almost similar findings were reported in a recent study of resource-sharing activities among agricultural libraries in Malaysia (Majid et al, 1999). It seems that the participants are strongly aware of the benefits of resource-sharing programs and, if an opportunity presented itself, they will fully support it.…”
Section: Perceptions Of Resource-sharing Activitiessupporting
confidence: 79%
“…It is interesting to note that almost similar findings were reported in a recent study of resource-sharing activities among agricultural libraries in Malaysia (Majid et al, 1999). It seems that the participants are strongly aware of the benefits of resource-sharing programs and, if an opportunity presented itself, they will fully support it.…”
Section: Perceptions Of Resource-sharing Activitiessupporting
confidence: 79%
“…The situation evolving in less developed countries is not very encouraging. For example, a study by Majid, Eisenschitz, and Anwar (1999) found that RS was basically limited to interlibrary lending and document delivery activities in the agricultural libraries in Malaysia. Only limited RS activity was observed among participating libraries in the Association of Southeast Asian Nations' region.…”
Section: Literature Reviewmentioning
confidence: 99%